Shakespeare between Machiavelli and Hobbes : dead body politics - Moore, Andrew, 1981- (Politics, literature, & film., 2016)
"Shakespeare between Machiavelli and Hobbes explores Shakespeare's political outlook by comparing some of the playwright's best-known works to the works of Italian political theorist Niccolò Machiavelli and English social contract theorist Thomas Hobbes. This ultimately reveals the materialist principles that underpin Shakespeare's imaginary states."--